Coupling ecosystem-centered governance modes with environmental justice - Cutts, Bethany B.; Greenlee, Andrew J.; Chantrill, Carolina V. (Frontiers in Sustainable Cities, 2022)
In North America, Great Lakes Areas of Concern (AOCs) were established to remediate aquatic pollution in 1987 as part of a binational agreement between the United State of America and Canada. Although the action preceded formal environmental injustice acknowledgment, the AOC program’s effort to remediate legacy pollutants includes language with the potential to accomplish core goals of EJ: democratizing decision-making and reducing disproportionate environmental burden. Yet, in AOCs, discussions of public engagement regarding AOC work tend to define participation institutionally (i.e. the state, market, and civil society) rather than by racial or socioeconomic inclusivity. Understanding how AOC governance processes consider representation of, and benefit to communities negotiating remediation decisions from positions of systemic disadvantage requires addressing the relationship between ecosystem-centered governance modes and environmental justice. In this study, interviews with governance actors reveal that concern for EJ issues wield different forms of authority as ecosystem-centered governance and environmental justice couple, decouple, and uncouple. Changes in coupling correspond with shifts in ecosystem-centric governance mode, but coupling does not rely on any one particular governance arrangement. Instead, coupling relies on leadership practices and conceptions of fairness that are EJ-responsive and present EJ as indistinct from ecosystem goals and targets. Our findings reinforce the assertion that ecosystem-centered governance can be reimagined to better facilitate EJ even without changes in financial and regulatory constraints. We conclude by proposing empirical measures that advance EGM-EJ qualitative scholarship and practical advice about how to cultivate EJ-responsive leadership in ecosystem-centered governance arrangements.